Virtual reality distraction for patients to relieve pain and discomfort during colonoscopy - Govert Veldhuijzen (Endoscopy International Open, 2020)
Background and study aims Colonoscopy is an invasive procedure that may cause patients pain and discomfort. Routine use of sedation, while effective, is expensive and requires logistical planning. Virtual reality (VR) offers immersive, three-dimensional experiences that distract the attention and might comfort patients. We performed a pilot study to investigate the feasibility of VR distraction during colonoscopy. Patients and methods Adults referred for colonoscopy were considered for inclusion and divided over two groups: with and without VR glasses. The main outcome was patient acceptance of wearing VR glasses during colonoscopy without compromising the technical success of the procedure. Secondary outcomes were patient comfort, pain, and anxiety before, during and after the procedure, using validated patient questionnaires. Patient comments were collected through a qualitative interview. Results We included 19 patients, 10 of whom were offered VR glasses. All patients accepted VR glasses without prolonging procedural time. No disadvantages of the VR glasses were reported in terms of communication or change of position of the patient. We found that patient comfort, pain, anxiety, and satisfaction in relation to the procedure were similar in both groups. Patients described a pleasant distracting effect using VR glasses. Conclusion VR glasses during colonoscopy are accepted by patients and do not compromise endoscopic technical success. Patients reported that the VR experience was pleasant and distracting.